Analysis of the Causal Relationship between Unemployment and Poverty - Khairuddin (Neo Journal of economy and social humanities, 2025)
This study aims to analyze the causal relationship between unemployment and poverty by reviewing previous research findings in both developing and developed countries. The method employed is a literature review using the SPIDER approach (Sample, Phenomenon of Interest, Design, Evaluation, Research Type). The reviewed sample focuses on the working-age population, the phenomenon of interest concerns the causal link between unemployment and poverty, the research design includes quantitative studies based on panel data, time series analyses, and causality tests, as well as relevant qualitative studies. The evaluation emphasizes the direction of the relationship and moderating factors, while the selected research type consists of empirical articles published between 2020 and 2025. Literature searches were conducted through Google Scholar, PubMed, and ScienceDirect using the keywords poverty, unemployment, causality, nexus, kemiskinan, and pengangguran, resulting in 20 articles that met the inclusion criteria. The findings indicate that most studies reveal a one-way causal relationship from unemployment to poverty, while others identify a bidirectional relationship, in which poverty also increases the risk of unemployment through limited access to education, skills, and social capital. Furthermore, job quality and social protection policies play a crucial role as moderating variables that may either weaken or strengthen the relationship between the two.